مبدأ سمو المعاهدات الدولية في القانون الوطني: قراءة في التعديلات الدستورية الجزائرية (مجلة الواحات للبحوث والدراسات, 2015)
The legal study of the articles 17/111, 124, 158, 159, and 160 of the 1976 Constitution shows that the Algerian legislator has granted to international treaties three different orders; the first rank is that of being superior to law when approved by the president of the republic according to the legally set forth measures, while those treaties were in the second rank given lawful degree (ordinary legislation) if also approved by the president of the republic. They were, too, issued in the Official Journal after they were approved by the leading entity of the party and the National People’s Assembly.In the 3rd rank the Algerian legislator has implicitly granted a superior degree over the Constitution to treaties that don’t need parliamentary and political approval in that the rule requires that states shouldn’t advance their national rules to evade their international commitments.Though in the 1989 and 1996 Constitutions, it was noted that the Algerian legislator has granted to international treaties four different ranks; the first rank granted was lower to the Constitution (the principal of superiority of Constitution over treaties). The second rank was that of superiority over the Constitution if approved according to clauses set forth in the Constitution (full approval). However, if approved as contrary to those clauses (partial approval), the treaties will, it is noted, have the same rank of the national legislation.Moreover, it can be said that the legislator has given a superior rank over Constitution to international treaties that don’t need parliamentary approval.